Crm1-Dependent Nuclear Export of Bach1 is Involved in the Protective Effect of Hyperoside on Oxidative Damage in Hepatocytes and CCl4-induced Acute Liver Injury - Cai Y; Li B; Peng D; Wang X; Li P; Huang M; Xing H; Chen J (Dove Medical Press, 2021)
Yongqing Cai1 *,* Bin Li1 *,* Dan Peng,1 Xianfeng Wang,1 Pan Li,2 Mingchun Huang,3 Haiyan Xing,1 Jianhong Chen1 1Department of Pharmacy, Daping Hospital, Army Medical University, Chongqing, 400042, People’s Republic of China; 2Department of Pharmacy, Fengdu Traditional Chinese Medicine Hospital, Chongqing, 408299, People’s Republic of China; 3Department of Pharmacy, Chongqing Traditional Chinese Medicine Hospital, Chongqing, 400021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianhong ChenDepartment of Pharmacy, Daping Hospital, Army Medical University, Chongqing, 400042, People’s Republic of ChinaTel +86 23 6875 7091Email chenjh-110@263.netBackground: Nrf2-Bach1 antioxidant signaling pathway is considered as one of the most important mechanisms of cellular resistance to oxidative injury. The effect of hyperoside (Hyp) on the expression and distribution of Bach1, the relationship of Hyp’s antioxidative effect and the influence of Bach1 remains unclear.Purpose: The aim of this study was to investigate the role and mechanisms of Bach1 in the protective effect of Hyp on oxidative liver injury.Methods: The protective effect of Hyp on oxidative stress injury was observed in vivo and in vitro. Next, the influence of Hyp on Bach1 expression and distribution, and competitive combination of Nrf2-Bach1 with ARE in H2O2-induced L02 cell was studied by Western blot, RT-PCR, immunofluorescence and CHIP assay. Finally, the expressions of Crm1, ERK and p38 and their roles on Hyp mediated nuclear export of Bach1 were investigated by Western blot.Results: Hyp ameliorated the pathological damage, reduced the liver index, AST, ALT and MDA activities, and increased SOD and GSH levels in the CCl4-induced acute liver injury mouse model. Hyp attenuated H2O2-induced oxidative stress injury in L02 cells. Hyp promoted the early rapid redistribution of Bach1 from nucleus to cytoplasm. CHIP analyses demonstrated that Hyp enhanced the levels of Nrf2-ARE complex, and weakened the levels of Bach1-ARE complex within three hours. In addition, Hyp enhanced transport protein Crm1 expression and ERK1/2 activity. And LMB, a Crm1 inhibitor, attenuated the effect of Hyp on Bach1 nuclear export and anti-oxidation. U0126, an ERK1/2 inhibitor, reduced the effect of Hyp on Crm1 expression and the Bach1 redistribution.Conclusion: The hepatoprotective mechanism of Hyp was related to improve Bach1 nuclear export depending on ERK1/2-Crm1 to upregulate the level of Nrf2 binding to ARE.Keywords: hyperoside, oxidative stress, Bach1, Crm1, hepatoprotective